Maximum allowable contrast dose and prevention of acute kidney injury following cardiovascular procedures. Issue 2 (March 2018) - Aoun, Joe; Nicolas, Diala; Brown, Jeremiah R.; Jaber, Bertrand L.
Abstract : Purpose of review: Contrast-induced acute kidney injury (CI-AKI) is a serious complication. Although nonmodifiable and modifiable risk factors have been thoroughly characterized, the utility of the maximal allowable contrast dose (MACD) has not received adequate attention. The focus of this review is to provide a critical appraisal of this modifiable risk factor. Recent findings: Several retrospective and prospective cohort studies have demonstrated that the incidence of CI-AKI among patients receiving contrast media in volumes exceeding the MACD is consistently higher compared with those who do not exceed the MACD (an average of 24 vs. 6%). Furthermore, the MACD is independent predictor of CI-AKI and other adverse events. A two-step algorithm incorporating the determination of the MACD and the contrast volume to eGFR ratio prior to a planned cardiovascular procedure is a sound approach to minimize contrast volume and prevent CI-AKI. Summary: Prevention of CI-AKI must remain a clinical priority. Intraprocedural preventive measures should include a priori calculation of the MACD and contrast volume to eGFR ratio to limit contrast volume. Other measures may include the adoption of the transradial approach, the use of automated contrast injectors and small catheters to limit contrast volume, the use of low-osmolar contrast agents, and if necessary the use of staged procedures. We call for the system-wide implementation of evidence-based care bundles to prevent CI-AKI.